Generation of a membrane potential by sodium-dependent succinate efflux in Selenomonas ruminantium. - Michel, T A (1990)
When Selenomonas ruminantium HD4 was grown in a chemostat, maximal succinate production and the highest molar growth yield values were both observed at a dilution rate of roughly 0.2 h-1. To determine the possible relationship between succinate efflux and high molar growth yields, the generation of a membrane potential by succinate efflux was studied in whole cells and vesicles (inside-out and right-side-out) prepared from S. ruminantium. Washed whole cells took up succinate in the absence of an exogenous energy supply; uptake was completely abolished by brief treatment with dinitrophenol or with nigericin and valinomycin. High levels of sodium ions (with respect to the intracellular sodium concentration in the assay buffer had a stimulatory effect on succinate uptake. When succinate was added to inside-out vesicles, a membrane potential (inside positive) was generated, as indicated by fluorescence quenching of the anionic lipophilic dye Oxonol V. Fluorescence quenching was sensitive to uncoupling by gramicidin D but only partially sensitive to the uncoupler carbonyl cyanide-p-trifluoromethoxyphenylhydrazone. In right-side-out vesicles, succinate uptake could be driven by an artificially imposed sodium gradient but not by a potassium diffusion potential; imposition of both a sodium gradient and potassium diffusion potential resulted in improved succinate uptake. The generation of a membrane potential (inside negative) upon succinate efflux was demonstrated directly in right-side-out vesicles when succinate-loaded vesicles were diluted into succinate-free buffer, and the lipophilic cationic probe tetraphenylphosphonium accumulated in the vesicles. Results indicate that an electrogenic succinate-sodium symporter is present in S. ruminantium. Transport of succinate out of the cell via the symporter might be responsible for the high molar growth yields obtained by this organism when it is grown at dilution rates where maximal succinate production occurs.